Pengaruh Corporate Governance, Kompleksitas Operasi dan Kepemilikan Asing Terhadap Audit Delay dengan Implementasi IFRS sebagai Variabel Moderasi - Faris Quraizhiy; Ahalik (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research aims to test and obtain empirical evidence of corporate governance, complexity of operaton and foreign ownership on audit delay with ifrs implementation as moderate variable. The population in this research are companies did initial public offering in indonesia stock exchange on period 20142016.. The number of research samples obtained is 51 companies with purposive sampling method and the amount of research data obtained is 153. The data analysis method used is multiple linier regression and moderate regression analysis. The simultaneous test shows that commisioner board, independent board of commisioner, audit committee, complexity of company and foreign ownership affect simultaneously on audit delay. The partial test results show thai board size, independent board and foreign ownership has negative affect on audit delay. Meanwhile audit committee and complexity of operation has positive affect on audit delay. Furthermore ifrs implementation doesn't moderate any effect from independent variable on audit delay.